O pensamento crítico do estudante de psicologia sobre sua formação - Henrique Pereira Aquino (2013)
This work was born from the interest in conducting a study on training in psychology. The main objective was to investigate if the psychology student has a critical thought about the training he/she is receiving. In this way, an overview about the knowledge produced on the training of psychologists in Brazil was traced. Discussions were made about the identity of the professional psychologist, of the Brazilian psychologist training and of the Brazilian market and, finally, of the Curriculum Guidelines for psychology courses in the country. Phenomenology was the methodological framework used in the collection and understanding of data. From semi-structured interviews with three final year students of psychology course at UFMG, it was possible to know the meanings expressed of their experiences forward to their degree. It was observed that the ideals of the students interviewed about the psychology course offered by UFMG, as well as the importance of the institution of national recognition, cross in a forceful way the assessments made on the training they are receiving. In the present study, it was understood that the critical thinking of the students of psychology would be that ability to undertake a rational discussion about the course of their training, reflect on the acquired/produced knowledge, recognizing the breadth and diversity of psychology as a science, as well as the nature of professional practice and ultimately, the limits and possibilities of the training of the psychologist during the under graduation time. Therefore, having this reference and based on interviews conducted it was found that, in general, the students did not perform a critic of the training towards the "creation of critical spirit."